Dynamic rock tensile strengths of Laurentian granite: Experimental observation and micromechanical model - Kaiwen Xia; Wei Yao; Bangbiao Wu (Journal of Rock Mechanics and Geotechnical Engineering, 2017)
Tensile strength is an important material property for rocks. In applications where rocks are subjected to dynamic loads, the dynamic tensile strength is the controlling parameter. Similar to the study of static tensile strength, there are various methods proposed to measure the dynamic tensile strength of rocks. Here we examine dynamic tensile strength values of Laurentian granite (LG) measured from three methods: dynamic direct tension, dynamic Brazilian disc (BD) test, and dynamic semi-circular bending (SCB). We found that the dynamic tensile strength from direct tension has the lowest value, and the dynamic SCB gives the highest strength at a given loading rate. Because the dynamic direct tension measures the intrinsic rock tensile strength, it is thus necessary to reconcile the differences in strength values between the direct tension and the other two methods. We attribute the difference between the dynamic BD results and the direct tension results to the overload and internal friction in BD tests. The difference between the dynamic SCB results and the direct tension results can be understood by invoking the non-local failure theory. It is shown that, after appropriate corrections, the dynamic tensile strengths from the two other tests can be reduced to those from direct tension.